Cardiometabolic consequences of maternal hyperandrogenemia in male offspring. Issue 14 (20th July 2021) - Zuchowski, Yvonne; Dalmasso, Carolina; Shawky, Noha M.; Reckelhoff, Jane F.
Abstract: Polycystic ovary syndrome (PCOS) in women is characterized by hyperandrogenemia, obesity, and oligo‐ or anovulation. In addition, women with PCOS are often obese, with insulin resistance, hyperlipidemia, and elevated blood pressure. The cardiometabolic consequences for the male offspring of maternal hyperandrogenemia are unclear. The present studies tested the hypothesis that male offspring of a rat model of PCOS would develop cardiometabolic disease as adults. Female Sprague–Dawley rats (hyperandrogenemic females (HAF)) were implanted with dihydrotestosterone or placebo pellets (controls) at 4 weeks of age, and were mated at 10–12 weeks and allowed to lactate their offspring after birth. Body weights in male HAF offspring were lower at birth than in controls until postnatal day 4, but body weights remained similar between male control and HAF offspring from 2 to 8 weeks of age. However, at 16 weeks of age, body weight was lower in HAF male offspring, but there were no differences in fat mass or lean mass factored for body weight in HAF males, compared to controls. Plasma total cholesterol and HDL and proteinuria were higher and nitrate/nitrite excretion was lower in male HAF offspring than in controls. Baseline blood pressure was similar between HAF male offspring and controls, but HAF offspring had an exaggerated pressor response to angiotensin II infusion. These data suggest that adult sons of PCOS mothers may be at increased risk of cardiometabolic disease. Abstract : Adult male offspring of a rat model of polycystic ovary syndrome is born small compared to controls, and as adults have lower body weights, with higher cholesterol and proteinuria. Although the male PCOS offspring have similar blood pressure as controls, they have an exaggerated pressor response to angiotensin II. These data suggest that male offspring of PCOS women may develop cardiometabolic disease as adults or with aging.